Tuberous Sclerosis Associated with Polycystic Kidney Disease: Effects of Rapamycin after Renal Transplantation - C. Rosado; P. García-Cosmes; P. Fraile; F. Vázquez-Sánchez (Case Reports in Transplantation)
Tuberous sclerosis is rarely associated with autosomal dominant polycystic kidney disease in the so-called tuberous sclerosis complex. This association leads to an increased frequency of end-stage renal disease. We present a patient suffering from both syndromes, who received a renal graft and anticalcineurinic drugs as immunosuppressive agents. Progressive titration of the drug was necessary in order to attain the effective doses due to the enzymatic induction caused by concomitant treatment with antiepileptic drugs. These high doses resulted in nephrotoxicity. Immunosuppressor treatment was switched to rapamycin, whereby an improvement in renal function and other signs of tuberous sclerosis and polycystic kidney disease was observed. This case report highlights both the efficacy and safety of rapamycin as an immunosuppressor treatment and its capacity for controlling other symptoms of these genetic-related disorders.